Analysis of the Influence of Islamic Corporate Governance (ICG) and Sharia Compliance on Fraud Prevention - Wulida Oktihandani; Indah Oktari Wijayanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study investigates how Islamic Corporate Governance (ICG) and Sharia Compliance impact the prevention of fraud in Sharia Commercial Banks and Sharia Business Units during the observation period of 2021-2023. It also, examines whether these two aspects have a real or symbolic influence, given that previous findings show a mismatch between normative governance structures and the effectiveness of their implementation. The Sharia Supervisory Board, Board Commissioners, and Board Directors contribute to the establishment of Islamic Corporate Governance. The Islamic Income Ratio (IsIR) and Profit Sharing Ratio (PSR) are used to evaluate compliance with Sharia principles. The dependent variable fraud calculated by calculating amount audits internal. Research studied all Islamic Commercial Banks and Business Units Indonesia from 2021-2023. Sample selected using purposive sampling method. Data obtained from annual report for the year 2021-2023 was processed using Eviews 12. The findings of the research indicate that the Board of Commissioners has a favourable impact on preventing fraud, whereas the Sharia Supervisory Board, Board of Directors, Islamic Income Ratio (IsIR), and Profit Sharing Ratio (PSR) do not contribute to fraud prevention. It should be noted that the adjusted R-squared value in this study is a modest 11.354%. The Sharia Compliance variable is determined based on only two indicators, namely the Islamic Income Ratio (IsIR) and Profit Sharing Ratio (PSR).